Anomalous and Not-So-Common Behavior in Common Ionic Liquids and Ionic Liquid-Containing Systems - Esperança, José M. S. S.; Tariq, Mohammad; Pereiro, Ana B.; Araújo, João M. M.; Seddon, Kenneth R.; Rebelo, Luis Paulo N. (Frontiers in Chemistry, 2019)
This work highlights unexpected, not so well known responses of ionic liquids and ionic liquid-containing systems, which are reported in a collective manner, as a short review. Examples include: (i) Minima in the temperature dependence of the isobaric thermal expansion coefficient of some ILs; (ii) Viscosity Minima in binary mixtures of IL + Molecular solvents; (iii) Anomalies in the surface tension within a family of ILs; (iv) The constancy among IL substitution of Cp/Vm at and around room temperature; (v) ILs as glass forming liquids; (vi) Alternate odd-even side alkyl chain length effects; (vii) Absolute negative pressures in ILs and IL-containing systems; (viii) Reversed-charged ionic liquid pairs; (ix) LCST immiscibility behavior in IL + solvent systems.